Croncise organocatalytic route to protected (2S, 4R)-4-hydroxyornithine and(+)-pseudohygroline - Jha, Vishwajeet; Kumar, Pradeep (Synlett, 2014)
A practical, efficient, and organocatalytic approach to the synthesis of (2S,4R)-4-hydroxyornithine and (+)-pseudohygroline is reported using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and Horner-Wadsworth-Emmons olefination reaction of an aldehyde as the key step.
Keywords: aldehydes; Amination; Amino alcohols; cyclization; Enantioselectivity; Wittig reaction